2009
DOI: 10.1002/hep.22976
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the patient with hepatitis B #

Abstract: The initial evaluation of a patient with hepatitis B virus infection should attempt to assess the disease activity and stage in the context of the known natural history of this infection and to properly assess the needs for treatment and surveillance. In addition to a medical history and focused physical examination, the initial evaluation usually requires serological, biochemical, and virological tests to confirm the diagnosis as well as an imaging study to establish a baseline for future monitoring. A liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 32 publications
1
33
0
6
Order By: Relevance
“…Les patients atteints d'hépatite chronique B sont à risque de développer un CHC. Les facteurs de risques spécifiques sont : l'âge, le sexe masculin, l'origine africaine ou asiatique, les cas familiaux de CHC et la charge virale élevée [24]. Trois de nos patients vont développer un CHC (un par non-respect du suivi médical, et deux par manque de moyens financiers).…”
Section: Cirrhose Et Chcunclassified
See 1 more Smart Citation
“…Les patients atteints d'hépatite chronique B sont à risque de développer un CHC. Les facteurs de risques spécifiques sont : l'âge, le sexe masculin, l'origine africaine ou asiatique, les cas familiaux de CHC et la charge virale élevée [24]. Trois de nos patients vont développer un CHC (un par non-respect du suivi médical, et deux par manque de moyens financiers).…”
Section: Cirrhose Et Chcunclassified
“…Le faible taux de résistance (6,7 %) dans notre étude est dû au petit nombre de patients traités et à la durée du suivi. Malgré son taux de résistance élevé, de nombreux auteurs rapportés par Zoulim [30] Dans la littérature, il a été rapporté que les patients qui ont des ALAT subnormales (une à deux fois la limite supérieure de la normale) présentent, à l'examen histologique, une activité inflammatoire minime à modérée et une fibrose moindre par rapport à ceux qui ont des ALAT élevées (risque plus élevé de progression de la maladie) [24].…”
Section: Indications Des Traitements Antivirauxunclassified
“…Overt HBV infection is characterized by the presence of HBsAg, which is secreted by infected hepatocytes (4,5). HBsAg levels have been suggested to i) reflect the presence of covalently closed circular DNA (cccDNA), ii) predict HBsAg seroclearance and iii) predict the therapeutic response during antiviral therapy (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1960s, hepatitis B virus surface antigen (HBsAg) has been the hallmark of HBV infection with concentrations reaching several hundred micrograms per millilitre 2. Recently, studies with newly available automated quantitative assays have shown that serum HBsAg levels vary significantly during the different phases of chronic HBV infection and are inversely correlated with the immune control of HBV: the higher control, the lower HBsAg level 3–6.…”
Section: Introductionmentioning
confidence: 99%